Eksistensi Regulasi Kekerasan Berbasis Gender Online Ditinjau Berdasarkan Perspektif Ius Constitutum Dan Ius Constituendum - Jhody Delviero; Fitrani Dewi Zarqa; Muhammad Adli Yanuari Saputra; Mutiara Khairani Agustia Wijaya (Peneliti.net, 2023)
Entering the era of society 5.0, various digital-based crimes have emerged that have hit people's lives, one of which is Online Gender-Based Violenc). KBGO is identified as an act of violence that directly targets an individual based on that person's gender and is facilitated by computer technology. Facts in the field reveal that not all types of KBGO are accommodated in legal products and laws and regulations in Indonesia. The non-accommodation of all types of KBGO certainly has bad implications for the community and hinders the implementation of the legal process. This study aims to determine the results of the analysis of Indonesia's current positive law (ius constitutum) with future legal ideals (ius constituendum). The type of research used in this article is normative juridical research and uses normative approach. Based on the results of the analysis conducted, it was found that the current ineffectiveness of Indonesian laws and regulations in tackling and providing legal protection to victims of KBGO. Therefore, a review of laws and regulations is needed to accommodate and ensnare all types of KBGO crimes and provide legal protection to victims.